Molecular and biological characterization of infectious full-length cDNA clones of two viruses in Paris yunnanensis, including a novel potyvirus - Pingxiu Lan; Peng He; Aiqiu Mu; Mengji Cao; Yun Wang; Guohua Zhou; Xiaojiao Chen; Hong Cai; Fan Li (Scientific Reports)
Abstract Paris yunnanensis, also named as Rhizoma Paridis in the Chinese Pharmacopeia, is a perennial Chinese medicinal herb commonly grown in Southwest China. However, several viruses have been found infecting this plant in recent years. Using high-throughput sequencing (HTS) and Sanger sequencing, this study obtained the complete genome sequences of three capillovirus isolates and one potyvirus isolate. Genomic and phylogenetic analyses revealed that these three capillovirus isolates are the same virus as the newly reported capillovirus, Paris polyphylla chlorotic mottle virus. The newly found potyvirus isolate shares 52.4–68.9% nucleotide sequence identity with other known potyviruses and thus, is grouped into the bean common mosaic virus subgroup. Based on the nucleotide sequence identity, we consider this virus a novel potyvirus species and propose ‘Paris potyvirus 5’ (ParPV-5) as its common name, and ‘Potyvirus shilinense’ as its species name. To characterize their biological features, two infectious clones, representing the two viruses, have been constructed through homologous recombination or yeast homologous recombination, and inoculated to several species plants, respectively. The results showed both of the viruses can infect P. yunnanensis and Nicotiana benthamiana. In addition, Paris polyphylla chlorotic mottle virus (PpCMV) can infect N. tabacum var. Xanthi nc, Cucurbita moschata, and Capsicum annuum, and ParPV-5 can infect Cucumis sativus L. and Bidens pilosa L. However, except mild leaf deformation exhibited on the PpCMV-inoculated C. moschata plants, no obvious symptom were observed in these plants including P. yunnanensis. A total of 179 field P. yunnanensis leaf samples from four counties in 2020–2021, and all 640 P. yunnanensis plants from a whole study plot of Lijiang in 2024, were tested using RT-PCR and specific primers, the results showed that PpCMV is a potential preponderant species in some regions, and ParPV-5 has the possible transmission from the original site to other regions.